Interfaces entre o trabalho profissional do/a assistente social e a questão agrária no Brasil: um estudo a partir da produção do conhecimento no Serviço Social - Fonzar, Juliana Firmino (2024)
The agrarian question is at the core of Brazil’s socio-historical formation. It is an expression of the social question – a fertile and complex field for social workers’ practice. However, it is a topic that is seldom addressed in education and in the spaces for debate and knowledge production within the profession, which affects its visibility, understanding, and analysis by social workers. This study focuses on the professional work of social workers within the scope of the agrarian question. In this context, the general objective is to identify and understand the interfaces between social workers’ professional work and the Agrarian Question in Brazil, based on the scientific production in Social Work from 2012 to 2022. To achieve this goal, a methodological process anchored in a qualitative approach is proposed, using exploratory research, grounded in historical-dialectical materialism. The methodological trajectory involved conducting bibliographic and documentary research based on theses and dissertations found in the databases of the libraries and virtual repositories of Social Work Graduate Programs, area 32 of CAPES; works from the The Brazilian Congresses of Social Workers (Congressos Brasileiros de Assistentes Sociais - CBASs); and The International Public Policy Conferences (Jornadas Internacionais de Políticas Públicas - JOINPPs), from 2012 to 2022. The research results indicate that scientific production in Social Work addresses the professional work of social workers in rural areas through field research, bibliographic, documentary research, and experience reports, establishing interfaces between this work and the agrarian question in the context of professional education and practice. It is concluded that the agrarian question category needs to be further explored in professional education to provide subsidies for competent professional practice in the theoretical-methodological, ethical-political, and technical-operational dimensions. As an expression of the social question, the agrarian question represents a suitable field for professional work, which has predominantly occurred through the mediation of social policy.